ANALISIS USAHATANI DAN PEMASARAN HANJELI (COIX LACRYMA-JOBI L) DI DESA TANJUNG NIUR KECAMATAN TEMPILANG KABUPATEN BANGKA BARAT - Evahelda Evahelda; Dhea Aprilia; Muntoro Muntoro (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
The study’s aims were (1) Calculating the feasibility of hanjeli farming, and (2) Describing the marketing channel for hanjeli farming. This study was conducted from December 2022 to July 2023 in Tanjung Niur Village, Tempilang District, West Bangka Regency. The study was conducted using case study method on sample of 10 hanjeli farmers who selected using saturated sample method. The data used in this study was collected through observation, interview, and questionnaire. These data were analyzed using analysis of income, price breakeven point, production breakeven point, revenue breakeven point, and R/C ratio. The studys’ results were (1) Average R/C ratio of hanjeli farming in Tanjung Niur Village was 5, means every Rp. 1 in production costs incurred will receive revenue of Rp. 5; and, (2) Hanjeli farming in Tanjung Niur Village has one marketing channel, namely zero level marketing channel, where marketing channel shows direct sales from farmers to consumers.